Autophagy-Mediated Defense Response of Mouse Mesenchymal Stromal Cells (MSCs) to Challenge with Escherichia coli - Gorbunov, N.V.; Garrison, B.R.; Zhai, M.; McDaniel, D.P.; Ledney, G.D.; Elliott, T.B.; Kiang, J.G. (IntechOpen, 2012)
None